Non-random association between alleles detected at D4S95 and D4S98 and the Huntington's disease gene. Issue 11 (November 1989) - Theilmann, J; Kanani, S; Shiang, R; Robbins, C; Quarrell, O; Huggins, M; Hedrick, A; Weber, B; Collins, C; Wasmuth, J J
Abstract : Analysis of many families with linked DNA markers has provided support for the Huntington's disease (HD) gene being close to the telomere on the short arm of chromosome 4. However, analysis of recombination events in particular families has provided conflicting results about the precise location of the HD gene relative to these closely linked DNA markers. Here we report an investigation of linkage disequilibrium between six DNA markers and the HD gene in 75 separate families of varied ancestry. We show significant non-random association between alleles detected at D4S95 and D4S98 and the mutant gene. These data suggest that it may be possible to construct high and low risk haplotypes, which may be helpful in DNA analysis and genetic counselling for HD, and represent independent evidence that the gene for HD is centromeric to more distally located DNA markers such as D4S90. This information may be helpful in defining a strategy to clone the gene for HD based on its location in the human genome.